2020
DOI: 10.17061/phrp30342012
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy and disparities in COVID-19–related knowledge, attitudes, beliefs and behaviours in Australia

Abstract: Objectives: To explore the variation in understanding of, attitudes towards, and uptake of, health advice on coronavirus disease 2019 (COVID-19) during the 2020 pandemic stage 3 restrictions ('lockdown') by health literacy in the Australian population.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
204
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 230 publications
(255 citation statements)
references
References 16 publications
14
204
1
2
Order By: Relevance
“…The data used in this study are from a prospective, longitudinal, national survey that launched in April 2020 and explored variations in people’s understanding of, attitude toward, and uptake of COVID-19 health advice during the 2020 pandemic [ 9 ]. Herein, we report on data from a survey wave conducted over a 1-week period (ie, June 5 to June 12, 2020) in Australia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data used in this study are from a prospective, longitudinal, national survey that launched in April 2020 and explored variations in people’s understanding of, attitude toward, and uptake of COVID-19 health advice during the 2020 pandemic [ 9 ]. Herein, we report on data from a survey wave conducted over a 1-week period (ie, June 5 to June 12, 2020) in Australia.…”
Section: Methodsmentioning
confidence: 99%
“…Participants who were aged ≥18 years, could read and understand English, and resided in Australia were recruited via paid targeted advertisements on social media (ie, Facebook and Instagram). More details on recruitment are provided in the McCaffery et al study [ 9 ]. Participants were given the opportunity to enter a prize draw for the chance to win 1 of 10 Aus $20 (US $14.62) gift cards upon completion of the survey.…”
Section: Methodsmentioning
confidence: 99%
“…The data used in this study are from a prospective, longitudinal, national survey in Australia that aimed to evaluate variation in the public's understanding, attitudes, and implementation of COVID-19 health advice during the first lockdown period in 2020 [17,18]. A total of 4362 participants were recruited between April 17 and 24, 2020; these participants completed the baseline survey (Round 1).…”
Section: Data Collectionmentioning
confidence: 99%
“…The European Health Literacy Survey conducted in eight countries demonstrated that 50% of adults have problematic or inadequate levels of access, understanding, appraisal and application of health or risk information [34,35]. A study in Australia showed that people with low health literacy and people whose native language is not English demonstrated poorer understanding of COVID-19 symptoms and prevention measures, more difficulty accessing government information, difficulty accessing prescription medication, and experienced greater anxiousness and financial difficulties [36]. Studies conducted in Australia and the United States showed that factors increasing vulnerability to COVID-19, such as age, underlying chronic diseases, and income are also factors associated with the ability to access and understand health information and decision-making [36,37].…”
Section: Risk Communicationmentioning
confidence: 99%
“…A study in Australia showed that people with low health literacy and people whose native language is not English demonstrated poorer understanding of COVID-19 symptoms and prevention measures, more difficulty accessing government information, difficulty accessing prescription medication, and experienced greater anxiousness and financial difficulties [36]. Studies conducted in Australia and the United States showed that factors increasing vulnerability to COVID-19, such as age, underlying chronic diseases, and income are also factors associated with the ability to access and understand health information and decision-making [36,37]. During the COVID-19 pandemic and widespread lockdown, digital media has become a convenient and rapid tool for people to gain information.…”
Section: Risk Communicationmentioning
confidence: 99%